Methods, Principles and Technologies of Organising of Teaching Target Languages - Qurbonova Gulnoza Ahmadjon qizi; Begmuratov Akmaljon Latifjon o'g'li (Research Parks Publishers, 2022)
Today, the study and teaching of foreign languages has become one of the priorities of the education system. It is well known that new reforms are being implemented at the state policy level. Therefore, new and innovative methods and techniques of teaching foreign languages are being introduced into science by experienced teachers and professors. This article describes in detail the methods, principles and technologies of organizing teaching target languages.